Prognostic value of coexisting conditions and complications in pleuroparenchymal fibroelastosis: a single-center retrospective study - Iwasaki, Kazuhiko; Watanabe, Satoshi; Kase, Kazumasa; Ohkura, Noriyuki; Saeki, Keigo; Tambo, Yuichi; Hara, Johsuke; Abo, Miki; Kimura, Hideharu; Yano, Seiji (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background: Pleuroparenchymal fibroelastosis (PPFE) is a rare idiopathic interstitial lung disease (ILD) characterized by subpleural parenchymal fibrosis and elastosis mainly in the upper lobes. PPFE occurs in a secondary form that overlaps with underlying medical conditions or complications. This study evaluated the clinical impact of coexisting factors on the survival of patients with PPFE. Methods: Fifty-five PPFE patients were retrospectively evaluated. The patients’ diagnoses were categorized as “idiopathic PPFE” with no known cause or “secondary PPFE” with underlying medical conditions or complications. The clinical characteristics and survival rates of these groups were compared. Results: Twenty-eight patients (50.9%) were diagnosed with idiopathic PPFE and 27 (49.1%) with secondary PPFE, including cases of occupational dust exposure, connective tissue disease (CTD), post-hematopoietic stem cell transplantation (HSCT), and a family history of ILD. The idiopathic and secondary PPFE groups had similar clinical features, laboratory tests, and pulmonary function profiles, including a low body mass index, normal Krebs von den Lungen-6, high surfactant protein-D, and high residual volume/total lung capacity. In the secondary PPFE group, post-HSCT was associated with a worse prognosis, and CTD was associated with better prognosis. A multivariate analysis demonstrated that post-HSCT and a reduced forced vital capacity were significantly associated with a worsened survival in patients with PPFE. Conclusions: The prognosis of PPFE is highly influenced by underlying medical conditions or complications. Patients with post-HSCT PPFE should be monitored particularly closely, as they are at higher risk of a poor prognosis than others.